A spatiotemporal study of gliosis in relation to depth electrode tracks in drug‐resistant epilepsy. (26th March 2014) - Goc, Joanna; Liu, Joan Y. W.; Sisodiya, Sanjay M.; Thom, Maria
Abstract Key questions remain regarding the processes governing gliogenesis following central nervous system injury that are critical to understanding both beneficial brain repair mechanisms and any long‐term detrimental effects, including increased risk of seizures. We have used cortical injury produced by intracranial electrodes (ICEs) to study the time‐course and localization of gliosis and gliogenesis in surgically resected human brain tissue. Seventeen cases with ICE injuries of 4–301 days age were selected. Double‐labelled immunolabelling using a proliferative cell marker (MCM2), markers of fate‐specific transcriptional factors (PAX6, SOX2), a microglial marker (IBA1) and glial markers (nestin, GFAP) was quantified in three regions: zone 1 (immediate vicinity: 0–350 μm), zone 2 (350–700 μm) and zone 3 (remote ≥2000 μm) in relation to the ICE injury site. Microglial/macrophage cell densities peaked at 28–30 days post‐injury (dpi) with a significant decline in proliferating microglia with dpi in all zones. Nestin‐expressing cells (NECs) were concentrated in zones 1 and 2, showed the highest regenerative capacity (MCM2 and PAX6 co‐expression) and were intimately associated with capillaries within the organizing injury cavity. There was a significant decline in nestin/MCM2 co‐expressing cells with dpi in zones 1 and 2. Nestin‐positive fibres remained in the chronic scar, and NECs with neuronal morphology were noted in older injuries. GFAP‐expressing glia were more evenly distributed between zones, with no significant decline in density or proliferative capacity with dpi. Colocalization between nestin and GFAP in zone 1 glial cells decreased with increasing dpi. In conclusion, NECs at acute injury sites are a proliferative, transient cell population with capacity for maturation into astrocytes with possible neuronal differentiation observed in older injuries.